Oriental Landscape in the Novel “Journey to the Orient” by G. de Nerval - T. V. Nuzhnaya (Научный диалог)
The presented article continues the cycle of the author’s research that reveals the specifics of the perception and artistic embodiment of various types of landscape space in French romantic prose. The relevance of the study is due to the appeal to the work of the unjustly forgotten French writer G. de Nerval, who in the novel “Journey to the Orient” was one of the first to acquaint the reader with the specifics of the eastern urban landscape, previously little known in European literature of the 19th century. Analysis of the novel shows that G. de Nerval tried to comprehend the East from different points of view: spiritual, ethnographic and literary and artistic. It is noted that the importance of describing the urban landscape for G. de Nerval testifies to his understanding of the importance  of the links between nature, culture and civilization. It is noted that the floral landscape has various functions in his work: historical, ethnographic and national. As a result, it was established that G. de Nerval in his novel was able to recreate a reliable picture of the East: its oriental landscape is saturated not only with exotic descriptions of flora and fauna, enlivened by the sounds of local nature, but also has valuable author’s comments  that give an idea of the national specifics of the plot.